The Role of Sharia Skepticism and Motivation in Gold-Backed Cryptocurrency Adoption Among Muslim Investors - Hasyim, Fuad; Ryandono, Muhammad Nafik Hadi; Musthofa, Wakhid (al-Uqud : Journal of Islamic Economics, 2026)
This study investigates the factors influencing the adoption of gold-backed cryptocurrencies (GBC) among Muslim investors in Indonesia, addressing the gap in understanding the interplay of psychological, social, and religious factors. While GBCs align with Islamic principles by avoiding gharar (uncertainty), maisir (speculation), and riba (interest), adoption remains hindered by sharia skepticism. Using a quantitative cross-sectional design with data from 357 respondents analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings highlight that attitudes, intrinsic and extrinsic motivations, and perceived sharia compliance significantly drive behavioral intention. However, sharia skepticism negatively moderates the attitude-intention relationship, presenting a substantial barrier. The study emphasizes the need for collaboration among regulators, fintech platforms, and religious authorities to address skepticism and foster trust through standardized governance. For businesses in Asia, these insights underline the importance of culturally aligned strategies, such as educational campaigns and partnerships with religious leaders, to enhance adoption in Islamic fintech markets.